Quartz tube kit and method suitable for thermal expansion test of high-modulus filamentous material

By designing a quartz tube kit suitable for high modulus filamentous materials, the problem of its thermal expansion performance testing is solved, stable installation and accurate measurement of samples at high temperatures is achieved, and the efficiency and accuracy of the test is improved.

CN119438296APending Publication Date: 2025-02-14AEROSPACE RES INST OF MATERIAL & PROCESSING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531400.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively test the thermal expansion properties of high modulus filamentous materials, especially due to their brittleness and high modulus, which lead to installation and measurement difficulties.

Method used

A quartz tube kit suitable for high modulus filamentous materials is designed, including quartz outer tube, quartz top rod, flange, gasket, quartz pulley and quartz round rod. Through special process and structural design, the bending curvature is reduced. , ensure stable installation and measurement of samples.

Benefits of technology

Reliable testing of the high-temperature thermal expansion performance of high-modulus filamentous materials is achieved, solving the problem of bending and breaking of samples at high temperatures, and improving the sensitivity and accuracy of measurement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438296A_ABST
    Figure CN119438296A_ABST
Patent Text Reader

Abstract

The invention discloses a quartz tube kit and a method suitable for thermal expansion testing of high-modulus filamentary materials, which can be used for testing thermal expansion coefficients of different types of filamentary materials, especially high-modulus / ultrahigh-modulus carbon fibers which are extremely easy to embrittle at room temperature to 1000 DEG C, and can be popularized and applied to thermal expansion performance testing of thin film materials. The quartz tube suite is composed of a quartz outer tube, a quartz ejector rod, a flange, a gasket, a quartz pulley and a quartz round rod. Wherein the quartz ejector rod, the gasket and the quartz round rod form an integrated ejector rod, the quartz outer tube, the flange and the quartz pulley form an integrated outer tube, the ejector rod is inserted into the outer tube, and the fit clearance is smaller than 2mm. The two ends of the detected filamentous material penetrate through the thin-wall red copper tube or the graphite tube, the lap joint is coated with an applicable organic or inorganic adhesive, and then the red copper tube is flattened. And after the adhesive is cured, soaking in acetone for not less than 24 hours, and mounting between the quartz pulley and the quartz round rod.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a quartz tube kit and method for thermal expansion testing of high modulus filamentary materials, and in particular to a quartz tube kit for thermal expansion testing of filamentary materials with a modulus of 50 to 800 GPa, belonging to the technical field of high-temperature thermal expansion performance detection and analysis of fiber materials. Background Art

[0002] With the rapid development of science and technology, more stringent requirements have been put forward for the thermal conductivity and thermal expansion properties of heat-resistant structural materials. In particular, in some important fields, many materials for high-temperature components require good heat dissipation performance, lightweight structural stiffness and corrosion resistance while maintaining dimensional stability. However, traditional heat dissipation materials have exceeded the performance limit and cannot meet the use requirements. However, mesophase pitch-based carbon fiber (MPCF) reinforced composite materials, represented by mesophase pitch-based carbon fiber, have great application potential in the fields of aerospace industry, high-end electronic equipment manufacturing, automotive parts materials, sporting goods, etc., because of their excellent properties such as ultra-high modulus, super thermal conductivity, electrical conductivity, electromagnetic shielding, low thermal expansion coefficient, strong corrosion resistance and wear resistance, low density, and light weight.

[0003] At present, domestic and foreign researchers' research on MPCF mainly focuses on two aspects: preparation technology and performance research. In terms of performance, in addition to the traditional mechanical properties, density, composition and microstructure evaluation and characterization, its thermal conductivity and thermal expansion properties are also the top priority. However, this type of fiber has a widely recognized disadvantage: because of the ultra-high elastic modulus, generally higher than 500GPa, or even as high as 800GPa, the elongation at break is generally not more than 0.3%, while the elastic modulus of stainless steel is generally 170-200GPa, and the elongation at break is 5%-60%. Compared with metals, it is extremely brittle. Even for ceramic materials with greater brittleness, its modulus is usually in the range of 300-400GPa, which is half as small as MPCF. Compared with ceramic materials, MPCF has extremely low compressive strength and bending strength due to its high brittleness, and is easily crushed and broken.

[0004] At present, there are some test methods and corresponding test conditions available for the evaluation and characterization of the thermal conductivity of MPCF. However, there are no directly available test methods and test equipment for the evaluation and characterization of its thermal expansion performance. Generally, it is made into a mesophase pitch-based carbon fiber (MPCF) unidirectional reinforced composite material. By testing the thermal expansion performance of the (MPCF) unidirectional reinforced composite material, the thermal expansion performance of the MPCF fiber is reversely deduced from the ideal mathematical model constructed. The accuracy of the data obtained in this way is difficult to verify, and its confidence will inevitably be greatly reduced. Summary of the invention

[0005] The technical problem solved by the present invention is to overcome the deficiencies of the prior art and provide a quartz tube kit and method suitable for thermal expansion testing of high modulus filamentary materials, so as to realize high-temperature thermal expansion performance testing of such filamentary samples.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] The invention discloses a quartz tube kit suitable for thermal expansion testing of high modulus filamentary materials, comprising: a quartz outer tube, a quartz mandrel, a flange, a gasket, a quartz pulley and a quartz round rod; wherein the flange is circular and has an inner hole at the center; the gasket is connected to one end of the quartz mandrel; the other end of the quartz mandrel is connected to the quartz round rod; two sides of the quartz outer tube are respectively and symmetrically fixedly connected to two quartz pulleys; the quartz outer tube and the quartz mandrel are both hollow circular tubes; the quartz outer tube passes through the inner hole of the flange and is fixedly connected to the flange; the quartz mandrel is sleeved in the quartz outer tube.

[0008] Furthermore, in the above-mentioned kit, holes are symmetrically provided on both sides of the lower end of the quartz mandrel and perpendicular to the line connecting the two quartz pulleys; the hole is an arched structure; the end near the quartz pulley is semicircular; the height of the arched structure is 25 to 35 mm, and the edges of both sides of the arched structure are vertical and smooth; the two end faces of the quartz round rod are respectively vertically fixedly connected to the inner surface of the hole; the lower end face of the quartz round rod is 8 to 12 mm away from the lower end face of the quartz mandrel; the width of one side of the arched structure is greater than the diameter of the quartz round rod.

[0009] Furthermore, in the above-mentioned kit, the wall thickness of the hollow circular tube is 1.5 to 3 mm; the outer diameter of the quartz mandrel is 1 to 3 mm smaller than the inner diameter of the quartz outer tube.

[0010] Furthermore, in the above kit, the diameter of the quartz outer tube is 20-28 mm and the length is 200-320 mm; the higher the test temperature, the longer the length of the quartz outer tube; the length of the quartz mandrel is 60-90 mm longer than the length of the quartz outer tube, and the roundness of the quartz outer tube and the quartz mandrel is no more than 0.02 mm.

[0011] Furthermore, in the above kit, the end face of the quartz outer tube is flush with the end face of the flange, and the flatness of the two is not greater than 0.02 mm; the verticality of the side wall of the quartz outer tube and the end face of the flange is not greater than 0.02 mm.

[0012] Furthermore, in the above kit, the diameter of the inner hole of the flange is 0.5 to 1 mm larger than the outer diameter of the quartz outer tube; the outer diameter of the flange is 8 to 12 mm larger than the outer diameter of the quartz outer tube; and the thickness of the flange is 4 to 6 mm.

[0013] Furthermore, in the above-mentioned kit, the gasket is in the shape of a disc, with a diameter 4 to 8 mm larger than the outer diameter of the quartz mandrel and a thickness of 2 to 4 mm; the verticality of the quartz mandrel and the gasket is no more than 0.02 mm.

[0014] Furthermore, in the above-mentioned kit, the quartz pulley includes a round tube and a baffle; wherein the baffle is connected to the end of the round tube; the outer diameter of the round tube is 8 to 12 mm, the wall thickness is 1 to 2 mm, and the length is 5 to 6 mm; the diameter of the baffle is 2 to 4 mm larger than the diameter of the round tube, and the thickness is 1.5 to 3 mm.

[0015] Furthermore, in the above kit, the quartz pulley is symmetrically welded to the end of the quartz outer tube away from the gasket at a distance of 10 to 20 mm.

[0016] Furthermore, in the above kit, high-purity fused quartz material treated with high-temperature dehydroxylation is used; the welding between the quartz outer tube and the quartz pulleys on the left and right sides, the welding between the quartz mandrel and the gasket, and the welding between the quartz round rod and the quartz mandrel are all treated with thermal stress relief.

[0017] A method for installing filamentary materials using a quartz tube kit suitable for thermal expansion testing of high modulus filamentary materials, characterized by comprising:

[0018] Cut the filament sample to be tested into a length of 320 to 360 mm;

[0019] Pass the filament sample to be tested through a thin-walled copper tube with a diameter not greater than 4 mm;

[0020] Overlap the two ends of the filament sample to be tested;

[0021] Evenly apply an organic or inorganic adhesive that is insoluble in acetone after curing to the overlap of the filament sample to be tested;

[0022] Move the thin-walled copper tube to the overlapped part after glue coating, flatten the thin-walled copper tube to make the overlapped part firmly connected to form a closed-loop circular filament sample to be tested;

[0023] Place the closed-loop circular filament sample to be tested in an oven at 160-180°C for 3-4 hours;

[0024] Take out the closed-loop circular filament sample to be tested after solidification and cooling, place it in an acetone solution, and soak it for no less than 24 hours to remove the sizing agent on the fiber surface to form a desizing circular sample;

[0025] The de-sizing round sample is pressed into a nearly elliptical structure to form a filamentary sample to be tested with a nearly elliptical structure;

[0026] The two ends of the elliptical structure of the filament sample to be tested are respectively hung on the quartz pulleys on the left and right sides of the quartz outer tube; the two long sides of the elliptical structure of the filament sample to be tested are passed around the lower end of the quartz round rod, and the quartz mandrel supports the elliptical structure of the filament sample to be tested;

[0027] Apply pressure to the quartz mandrel, and the elliptical filament sample to be tested is straightened by the gravity of the quartz mandrel and the external pressure.

[0028] The beneficial effects of the present invention and the prior art are:

[0029] (1) Since the thermal expansion coefficient of solid materials (usually linear expansion coefficient) refers to the ratio of the length change in a certain direction to its length in a standard laboratory environment when the temperature changes by 1°C. To measure the expansion coefficient, the temperature change and the length change must be measured simultaneously. For solid block materials, their shape is fixed within a certain range, and their length change is relatively easy to measure by contact or non-contact methods. However, for filamentary samples, the free state is generally irregularly curved, and a certain tension must be applied to the filamentary samples to straighten them, so that it is possible to obtain their length change when they are uniformly heated. Therefore, the present invention adopts a vertical quartz differential dilatometer method, that is, a vertical vertical differential dilatometer assembly is formed by a quartz outer tube and a mandrel made of the same stable material. When measuring temperature changes, the length of the filamentary sample relative to its outer tube or mandrel changes; the mandrel transmits the change in sample length to the displacement sensor, and the displacement sensor transmits the length change to the digital displacement meter, and displays and records the length change. To measure and record the length change of filamentary samples, the design of a suitable quartz differential dilatometer kit becomes the key, among which the design of the quartz outer tube and the quartz mandrel is particularly important.

[0030] (2) The present invention aims at solving the problem that high modulus filamentary samples to be tested are very easy to bend and break, and their high-temperature thermal expansion performance needs to be evaluated. The technical solution of reducing the bending curvature and large arc transition is adopted to solve the problem of high modulus filamentary samples breaking during installation. Therefore, quartz pulleys made of the same material are welded at high temperature on the outer surfaces of both sides of the quartz outer tube through a special process. The diameter of the quartz pulley depends on the modulus of the filamentary sample to be tested. The larger the modulus, the larger the diameter of the quartz pulley is, in order to further reduce the bending curvature. Similarly, the diameter of the quartz outer tube and the quartz top rod is appropriately increased, and the matching clearance between the quartz outer tube and the quartz top rod is 0.5 to 1.5 mm. In order to prevent the filamentary sample from slipping, a quartz baffle is welded on the other side of the quartz pulley.

[0031] (3) Similarly, a quartz cylinder with the same diameter as the quartz pulley is welded on the inner surface of the lower end of the quartz mandrel. In order to facilitate the filamentary sample to be tested to bypass the quartz cylinder without slipping, a semicircular arched structure hole with a height of 25 to 35 mm from the top to the bottom of the hole is symmetrically opened on the front and back sides of the lower end of the quartz mandrel. The edge of the hole is vertical and smooth. The two end faces of the quartz round rod are respectively welded to the inner surfaces on both sides of the hole. The welding point is 8 to 12 mm away from the lower end face, and its function is equivalent to the baffle of the quartz pulley.

[0032] (4) In order to improve the measurement sensitivity of the length change, the length difference between the quartz outer tube and the quartz mandrel is increased. The quartz mandrel is 60 to 90 mm longer than the quartz outer tube to increase the differential length change and solve the problem of low expansion coefficient filamentary samples being difficult to accurately test.

[0033] (5) How to securely mount the filamentary sample to be tested in a curved state on the quartz differential dilatometer is another urgent problem to be solved. To this end, the filamentary sample to be tested is cut into a length of about 320 to 360 mm, and is passed through a thin-walled copper tube with a diameter of no more than 4 mm from the left and right ends. An organic or inorganic adhesive that is insoluble in acetone after curing is evenly applied to the overlap of the filamentary sample, and then the copper tube is moved to the overlap after the adhesive is applied, and the copper tube is flattened to make the overlap firmly connected to form a closed-loop circular filamentary sample to be tested. The circular filamentary sample to be tested is placed in an oven and cured at 180°C for 3 to 4 hours. For fibrous filamentary samples to be tested, especially carbon fibers or high modulus carbon fibers, it is necessary to wait for curing and cooling, then take them out and place them in an acetone solution for at least 24 hours to remove the sizing agent on the fiber surface.

[0034] (6) The round sample after solidification and removal of the surface sizing agent is flattened toward the center, and the upper and lower ends are respectively suspended on the quartz pulleys on the left and right sides of the quartz outer tube, and the middle is passed around the lower end of the quartz round rod, and the push rod supports the sample to be tested. The gravity of the push rod and a certain external tension are used to straighten the filamentary sample to be tested that is suspended on the quartz pulley and passed around the lower end of the quartz round rod. In this way, when the sample to be tested and the quartz push rod are at the same temperature, the difference in expansion can be transmitted to the displacement sensor through the quartz push rod to achieve the purpose of measuring the length change, and then the thermal expansion coefficient of the filamentary sample to be tested is calculated by the derived formula. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is an assembly diagram of a quartz tube kit for thermal expansion testing of high modulus filamentary materials according to the present invention;

[0036] Among them: 1: quartz top rod upper end gasket; 2: quartz outer tube upper flange; 3: quartz outer tube; 4: quartz top rod; 5: quartz pulley; 6: quartz round rod;

[0037] Figure 2This is a structural diagram of the lower end of the quartz outer tube (3) of the present invention;

[0038] Figure 3 This is a structural diagram of the lower end of the quartz push rod (4) of the present invention;

[0039] Figure 4 This is a round filament sample with both ends bonded by thin-walled copper tubes;

[0040] Figure 5 The final installation diagram of the sample mounted on the quartz tube kit;

[0041] Figure 6 It is the measured original curve diagram of the length change of a certain high modulus carbon fiber to be tested as a function of temperature;

[0042] Figure 7 The figure is a curve diagram showing the relationship between the linear expansion coefficient in the length direction of the high modulus carbon fiber to be tested and the temperature. DETAILED DESCRIPTION

[0043] In order to make the purpose, content and beneficial effects of the present invention more clear, the following specifically describes the implementation mode of the present invention in conjunction with the drawings and examples.

[0044] like Figure 1 As shown, the present invention discloses a quartz tube kit suitable for thermal expansion testing of high modulus filamentary materials, comprising: a quartz outer tube, a quartz mandrel, a flange, a gasket, a quartz pulley and a quartz round rod; wherein the flange is circular and has an inner hole at the center; the gasket is connected to one end of the quartz mandrel; the other end of the quartz mandrel is connected to the quartz round rod; two sides of the quartz outer tube are symmetrically fixedly connected to two quartz pulleys respectively; the quartz outer tube and the quartz mandrel are both hollow circular tubes; the quartz outer tube passes through the inner hole of the flange and is fixedly connected to the flange; the quartz mandrel is sleeved in the quartz outer tube.

[0045] Preferably, holes are symmetrically provided on both sides of the lower end of the quartz mandrel and perpendicular to the line connecting the two quartz pulleys; the hole is an arched structure; one end near the quartz pulley is semicircular; the height of the arched structure is 25 to 35 mm, and the edges of both sides of the arched structure are vertical and smooth; the two end faces of the quartz round rod are respectively vertically fixedly connected to the inner surface of the hole; the lower end face of the quartz round rod is 8 to 12 mm away from the lower end face of the quartz mandrel; the width of one side of the arched structure is greater than the diameter of the quartz round rod.

[0046] Preferably, the hollow circular tube has a wall thickness of 1.5 to 3 mm; the outer diameter of the quartz mandrel is 1 to 3 mm smaller than the inner diameter of the quartz outer tube.

[0047] Preferably, the diameter of the quartz outer tube is 20-28 mm and the length is 200-320 mm; the higher the test temperature, the longer the length of the quartz outer tube; the length of the quartz mandrel is 60-90 mm longer than the length of the quartz outer tube, and the roundness of the quartz outer tube and the quartz mandrel is no more than 0.02 mm.

[0048] Preferably, the end face of the quartz outer tube is flush with the end face of the flange, and the flatness of the two is no greater than 0.02 mm; the verticality of the side wall of the quartz outer tube and the end face of the flange is no greater than 0.02 mm.

[0049] Preferably, the diameter of the inner hole of the flange is 0.5-1 mm larger than the outer diameter of the quartz outer tube; the outer diameter of the flange is 8-12 mm larger than the outer diameter of the quartz outer tube; and the thickness of the flange is 4-6 mm.

[0050] Preferably, the gasket is in the shape of a disc, with a diameter 4 to 8 mm larger than the outer diameter of the quartz mandrel and a thickness of 2 to 4 mm; the verticality of the quartz mandrel and the gasket is no greater than 0.02 mm.

[0051] Preferably, the quartz pulley comprises a round tube and a baffle, wherein the baffle is connected to the end of the round tube; the outer diameter of the round tube is 8 to 12 mm, the wall thickness is 1 to 2 mm, and the length is 5 to 6 mm; the diameter of the baffle is 2 to 4 mm larger than the diameter of the round tube, and the thickness is 1.5 to 3 mm.

[0052] Preferably, the quartz pulley is symmetrically welded to the end of the quartz outer tube away from the gasket at a distance of 10 to 20 mm.

[0053] Preferably, a high-purity fused quartz material treated with high-temperature dehydroxylation is used; the welding between the quartz outer tube and the quartz pulleys on the left and right sides, the welding between the quartz mandrel and the gasket, and the welding between the quartz round rod and the quartz mandrel are all treated with thermal stress removal.

[0054] A method for installing filamentary materials using a quartz tube kit suitable for thermal expansion testing of high modulus filamentary materials, characterized by comprising:

[0055] Cut the filament sample to be tested into a length of 320 to 360 mm;

[0056] Pass the filament sample to be tested through a thin-walled copper tube with a diameter not greater than 4 mm;

[0057] Overlap the two ends of the filament sample to be tested;

[0058] Evenly apply an organic or inorganic adhesive that is insoluble in acetone after curing to the overlap of the filament sample to be tested;

[0059] Move the thin-walled copper tube to the overlapped part after glue coating, flatten the thin-walled copper tube to make the overlapped part firmly connected to form a closed-loop circular filament sample to be tested;

[0060] Place the closed-loop circular filament sample to be tested in an oven at 160-180°C for 3-4 hours;

[0061] Take out the closed-loop circular filament sample to be tested after solidification and cooling, place it in an acetone solution, and soak it for no less than 24 hours to remove the sizing agent on the fiber surface to form a desizing circular sample;

[0062] The de-sizing round sample is pressed into a nearly elliptical structure to form a filamentary sample to be tested with a nearly elliptical structure;

[0063] The two ends of the elliptical structure of the filament sample to be tested are respectively hung on the quartz pulleys on the left and right sides of the quartz outer tube; the two long sides of the elliptical structure of the filament sample to be tested are passed around the lower end of the quartz round rod, and the quartz mandrel supports the elliptical structure of the filament sample to be tested;

[0064] Apply pressure to the quartz mandrel, and the elliptical filament sample to be tested is straightened by the gravity of the quartz mandrel and the external pressure.

[0065] The present invention can be applied to the thermal expansion performance testing of soft and brittle intermediate phase asphalt-based carbon fibers, high-strength and high-modulus carbon fibers and other hard and brittle filamentary materials at different temperatures, and belongs to the technical field of high-temperature thermal expansion performance testing and analysis of fiber materials. The purpose is to obtain high-temperature thermal expansion performance data of relevant filamentary temperatures up to 1000°C, and it can also be extended to film materials.

[0066] Example

[0067] like Figure 1 As shown, the present invention discloses a quartz tube kit suitable for thermal expansion testing of high modulus filamentary materials, comprising a quartz outer tube 3, a quartz mandrel 4, a flange 2, a gasket 1, a quartz pulley 5 and a quartz round rod 6.

[0068] The gasket 1 is melt-welded to the upper end of the quartz mandrel 4, and the quartz pulleys 5 are melt-welded to the left and right sides of the lower end of the quartz outer tube 3 respectively. The quartz outer tube 3 passes through the inner hole of the flange 2 from bottom to top, and the quartz outer tube 3 and the flange 2 are bonded by an inorganic adhesive. The quartz mandrel 4 welded with the gasket 1 passes through the quartz outer tube 3 from top to bottom, and the lower end of the quartz mandrel 4 is welded with a quartz round rod 6.

[0069] The quartz outer tube 3 and the quartz mandrel 4 are both hollow circular tubes with a wall thickness of 1.5 to 3 mm. The outer diameter of the quartz mandrel 4 is about 2 mm smaller than the inner diameter of the quartz outer tube 3. The outer diameter of the quartz outer tube 3 can be selected to be 20 to 28 mm, and the length is 200 to 320 mm. The higher the test temperature, the longer the length of the quartz outer tube 3 should be. The length of the quartz mandrel 4 is 60 to 90 mm longer than that of the quartz outer tube 3. The roundness of the quartz outer tube 3 and the quartz mandrel 4 are both required to be no more than 0.02 mm.

[0070] The upper end surface of the quartz outer tube 3 should be flush with the upper end surface of the flange 2, and the flatness of the two should not be greater than 0.02mm. The upper end surface of the quartz outer tube 3 and the upper end surface of the flange 2 should be perpendicular, and the perpendicularity is also not greater than 0.02mm.

[0071] The flange 2 is circular in shape and has an inner hole in the center. The diameter of the hole is 0.5 to 1 mm larger than the outer diameter of the quartz outer tube 3. The outer diameter of the flange 2 is 8 to 12 mm larger than the outer diameter of the quartz outer tube 3 and the thickness is 4 to 6 mm.

[0072] Figure 2 The structure diagram of the lower end of the quartz outer tube 3 is shown. There are two quartz pulleys 5, which are welded by a round tube and a baffle. The outer diameter of the round tube is about 8-12 mm, the wall thickness is about 2 mm, and the length is 5-6 mm. The diameter of the baffle is 2-4 mm larger than the diameter of the round tube, and the thickness is 1.5-3 mm. The quartz pulleys 5 should be welded symmetrically at a distance of 10-20 mm from the lower end of the quartz outer tube 3.

[0073] Figure 3 The figure shows the structure of the lower end of the quartz mandrel 4. The lower end of the quartz mandrel 4 has symmetrically opened holes with a rectangular bottom and a semicircular top. The height from the top to the lower end of the hole is 25 to 35 mm, and the edge of the notch or window is vertical and smooth. The two end faces of the quartz round rod 6 are respectively welded to the inner surface of the hole, 8 to 12 mm away from the lower end face, and the width of the notch or window on both sides should be moderately larger than the diameter of the quartz round rod 6.

[0074] All parts of the quartz tube kit are made of the same material - high-purity fused quartz that has been subjected to high-temperature dehydroxylation treatment. The molten welding needs to be subjected to heat-removing stress treatment, such as the welding between the quartz outer tube 3 and the quartz pulleys 5 on the left and right sides, the welding between the quartz mandrel 4 and the gasket 1, and the welding between the quartz round rod 6 and the quartz mandrel 4.

[0075] The quartz tube kit should be equipped with a suitable and firm displacement sensor bracket and a high-temperature heating furnace to be used for high-temperature thermal expansion coefficient testing of filamentary materials.

[0076] Figure 4 The figure shows a circular filament sample with two ends bonded by thin-walled copper tubes. The sample preparation process is as follows: the filament sample to be tested is cut into a length of about 320 to 360 mm, and is passed through thin-walled copper tubes with a diameter of no more than 4 mm from the left and right ends respectively. An organic or inorganic adhesive that is insoluble in acetone after curing is evenly applied to the overlap of the filament sample, and then the copper tube is moved to the overlap after the glue is applied, and the copper tube is flattened to make the overlap firmly connected to form a closed-loop circular filament sample to be tested.

[0077] Place the round filamentary sample to be tested in an oven and cure it at 180°C for 3 to 4 hours. For fibrous filamentary samples to be tested, especially carbon fiber or high modulus carbon fiber, it is necessary to wait for the solidification and cooling, then take it out and place it in an acetone solution for at least 24 hours to remove the sizing agent on the fiber surface.

[0078] Figure 5 The figure shows the final installation diagram of the sample installed on the quartz tube set. The installation process is: the round sample after curing and removing the surface sizing agent is flattened toward the center, and the upper and lower ends are respectively hung on the quartz pulleys 5 on the left and right sides of the quartz outer tube 3, and the lower end of the quartz round rod 6 is passed in the middle, and the quartz mandrel 4 supports the sample to be tested. The filamentary sample to be tested, which is suspended on the quartz pulley 5 and passed around the lower end of the quartz round rod 6, is straightened by the gravity of the quartz mandrel 4 and a certain external tension.

[0079] In this way, when the sample to be tested and the quartz mandrel 4 are at the same temperature, the difference in expansion can be transmitted to the displacement sensor through the quartz mandrel 4 to achieve the purpose of measuring the length change, and then the thermal expansion coefficient of the filamentary sample to be tested can be calculated by the derived formula.

[0080] Figure 6 The original curve of the measured length change of a certain high modulus carbon fiber to be tested with temperature. The horizontal axis in the figure is the measured temperature of the high modulus carbon fiber to be tested (the modulus is about 700GPa, usually greater than 400GPa is high modulus, much higher than the common metal 170~200GPa), and the vertical axis is the differential length change measured and recorded by the displacement sensor through the quartz mandrel. Figure 6 It can be seen that the quartz tube kit and related methods involved in the present invention can achieve the following conditions in the range of room temperature to 1000°C: the hard and brittle fibers are not broken, the change in fiber length can be smoothly transmitted in real time through the push rod, the structure does not become unstable or stuck, and the signal-to-noise ratio is good, thereby achieving the purpose of solving all the above-mentioned key problems.

[0081] Figure 7 The relationship curve between the linear expansion coefficient of the high modulus carbon fiber in the length direction and the temperature is shown in Figure 1. The horizontal axis is the measured temperature of the high modulus carbon fiber to be tested, and the vertical axis is Figure 6 The original data in the calculation is used to obtain the change of the linear expansion coefficient in the length direction with temperature through a certain formula. Figure 7 It can be seen that from room temperature to about 800℃, the linear expansion coefficient is negative, and it becomes positive above 800℃, and the value is very small, about 10 -7 It is 2 to 3 orders of magnitude lower than metals, ceramics, plastics, etc., and is truly a low-expansion hard and brittle fiber. It is precisely because of its negative expansion and high modulus characteristics that when it is compounded with metals, ceramics or plastics, new materials or products with near-zero expansion and high stiffness can be designed and applied to specific high-tech fields.

[0082] Parts of the present invention that are not described in detail belong to common knowledge among those skilled in the art.

Claims

1. A quartz tube kit suitable for thermal expansion testing of high modulus filamentary materials, characterized in that: include: A quartz outer tube (3), a quartz mandrel (4), a flange (2), a gasket (1), a quartz pulley (5) and a quartz round rod (6); wherein the flange (2) is circular and has an inner hole at the center; the gasket (1) is connected to one end of the quartz mandrel (4); the other end of the quartz mandrel (4) is connected to the quartz round rod (6); the two sides of the quartz outer tube (3) are symmetrically fixedly connected to two quartz pulleys (5); the quartz outer tube (3) and the quartz mandrel (4) are both hollow circular tubes; the quartz outer tube (3) passes through the inner hole of the flange (2) and is fixedly connected to the flange (2); the quartz mandrel (4) is sleeved in the quartz outer tube (3).

2. The quartz tube kit according to claim 1, characterized in that: The lower end of the quartz mandrel (4) is symmetrically provided with holes on both sides perpendicular to the line connecting the two quartz pulleys (5); the hole is an arched structure; one end near the quartz pulley (5) is semicircular; the height of the arched structure is 25 to 35 mm, and the edges of both sides of the arched structure are vertical and smooth; the two end faces of the quartz round rod (6) are respectively vertically fixedly connected to the inner surface of the hole; the lower end face of the quartz round rod (6) is 8 to 12 mm away from the lower end face of the quartz mandrel (4); and the width of one side of the arched structure is greater than the diameter of the quartz round rod (6).

3. The quartz tube kit according to claim 1, characterized in that: The wall thickness of the hollow circular tube is 1.5 to 3 mm; the outer diameter of the quartz top rod (4) is 1 to 3 mm smaller than the inner diameter of the quartz outer tube (3).

4. The quartz tube kit according to claim 1, characterized in that: The diameter of the quartz outer tube (3) is 20 to 28 mm, and the length is 200 to 320 mm; the higher the test temperature, the longer the length of the quartz outer tube (3); the length of the quartz top rod (4) is 60 to 90 mm longer than the length of the quartz outer tube (3), and the roundness of the quartz outer tube (3) and the quartz top rod (4) is no greater than 0.02 mm.

5. The quartz tube kit according to claim 1, characterized in that: The end face of the quartz outer tube (3) is flush with the end face of the flange (2), and the flatness of the two is no greater than 0.02 mm; the verticality of the side wall of the quartz outer tube (3) and the end face of the flange (2) is no greater than 0.02 mm.

6. The quartz tube kit according to claim 1, characterized in that: The diameter of the inner hole of the flange (2) is 0.5 to 1 mm larger than the outer diameter of the quartz outer tube (3); the outer diameter of the flange (2) is 8 to 12 mm larger than the outer diameter of the quartz outer tube (3); and the thickness of the flange (2) is 4 to 6 mm.

7. The quartz tube kit according to claim 1, characterized in that: The gasket (1) is in the shape of a disc, with a diameter 4 to 8 mm larger than the outer diameter of the quartz mandrel (4) and a thickness of 2 to 4 mm; the verticality of the quartz mandrel (4) and the gasket (1) is no greater than 0.02 mm.

8. The quartz tube kit according to claim 1, characterized in that: The quartz pulley (5) comprises a round tube and a baffle, wherein the baffle is connected to the end of the round tube; the outer diameter of the round tube is 8-12 mm, the wall thickness is 1-2 mm, and the length is 5-6 mm; the diameter of the baffle is 2-4 mm larger than the diameter of the round tube, and the thickness is 1.5-3 mm.

9. The quartz tube kit according to claim 1, characterized in that: The quartz pulley (5) is symmetrically welded to the end of the quartz outer tube (3) far away from the gasket (1) at a distance of 10 to 20 mm.

10. The quartz tube kit according to claim 1, characterized in that: High-purity fused quartz material that has been subjected to high-temperature dehydroxylation treatment is used; the welding between the quartz outer tube (3) and the quartz pulleys (5) on the left and right sides, the welding between the quartz mandrel (4) and the gasket (1), and the welding between the quartz round rod (6) and the quartz mandrel (4) are all subjected to heat-removing stress treatment.

11. A method for installing filamentary materials using the quartz tube kit for thermal expansion testing of high modulus filamentary materials according to any one of claims 1 to 10, characterized in that: include: Cut the filament sample to be tested into a length of 320 to 360 mm; Pass the filament sample to be tested through a thin-walled copper tube with a diameter not greater than 4 mm; Overlap the two ends of the filament sample to be tested; Evenly apply an organic or inorganic adhesive that is insoluble in acetone after curing to the overlap of the filament sample to be tested; Move the thin-walled copper tube to the overlapped part after glue coating, flatten the thin-walled copper tube to make the overlapped part firmly connected to form a closed-loop circular filament sample to be tested; Place the closed-loop circular filament sample to be tested in an oven at 160-180°C for 3-4 hours; Take out the closed-loop circular filament sample to be tested after solidification and cooling, place it in an acetone solution, and soak it for no less than 24 hours to remove the sizing agent on the fiber surface to form a desizing circular sample; The de-sizing round sample is pressed into a nearly elliptical structure to form a filamentary sample to be tested with a nearly elliptical structure; The two ends of the elliptical structure of the filament sample to be tested are respectively suspended on the quartz pulleys (5) on the left and right sides of the quartz outer tube (3); the two long sides of the elliptical structure of the filament sample to be tested are passed around the lower end of the quartz round rod (6), and the quartz top rod (4) supports the elliptical structure of the filament sample to be tested; Pressure is applied to the quartz mandrel (4), and the elliptical filament sample to be tested is straightened by the gravity of the quartz mandrel (4) and the external pressure.